RECREATION IN SPECIAL EDUCATION WITH PEOPLE WITH DOWN SYNDROME - Lopes Schabbach, Rosilene (Revista Gênero e Interdisciplinaridade, 2024)
This TCC aims to understand and discuss the process of including a child with Down syndrome in a regular school, contribute to the increase in studies on children with Down syndrome, recreation and psychomotor skills, and value and stimulate self-esteem with activities that allow them to create and recreate movements, experimenting and leading them to build positive values ​​and attitudes, given that the inclusion procedure, precisely because it differentiates the practice from integration, challenges common social systems to make fundamental changes in their procedures and structures. Social inclusion is, therefore, a process that contributes to the construction of a new type of society through transformations in physical environments, in the mentality of people and in the person with the disease. There must be inclusion in education, in leisure, in society, in the heart. When this is achieved, we can speak of inclusive life.